PERAN KOMITE SEKOLAH TERHADAP MUTU PENDIDIKAN MADRASAH IBTIDAIYAH - Mas’ud (MADINASIKA, 2020)
The research was motivated by the low quality of education in Madrasah Ibtidaiyah in Karangampel District, Indramayu Regency, one of the causes is thought to be due to the lack of role of the school committee. The research aims to determine: a) The role of the Madrasah Ibtidaiyah school committee, b) The quality of education in Madrasah Ibtidaiyah; c) The magnitude of the influence of the role of the school committee on the quality of education in Madrasah Ibtidaiyah. The approach used in this research is quantitative research with primary and secondary data collected through questionnaires. The data were processed and analyzed using a parametric statistical approach with descriptive analysis design and verification. The research results show that descriptively the role of the school committee and the quality of education are in good condition but there are still weaknesses in certain aspects. The results of the verification analysis show that the role of the school committee has a significant effect on the quality of education in Madrasah Ibtidaiyah with a magnitude of the effect of 00%, in the sense that the better the role of the school committee, the better the quality of education